Molecular cloning of the gene for the human placental GTP-binding protein Gp (G25K): identification of this GTP-binding protein as the human homolog of the yeast cell-division-cycle protein CDC42. - Shinjo, K (1990)
We have isolated cDNA clones from a human placental library that code for a low molecular weight GTP-binding protein originally designated Gp (also called G25K). This identification is based on comparisons with the available peptide sequences for the purified human Gp protein and the use of two highly specific anti-peptide antibodies. The predicted amino acid sequence of the protein is very similar to those of various members of the ras superfamily of low molecular weight GTP-binding proteins, including the N-, Ki-, and Ha-ras proteins (30-35% identical), the rho proteins (approximately 50% identical), and the rac proteins (approximately 70% identical). The highest degree of sequence identity (80%) is found with the Saccharomyces cerevisiae cell-division-cycle protein CDC42. The human placental gene, which we designate CDC42Hs, complements the cdc42-1 mutation in S. cerevisiae, which suggests that this GTP-binding protein is the human homolog of the yeast protein.